The expression of apoptosis-regulating proteins Bcl-2 and Bad in liver cells of C57Bl/6 mice under light-induced functional pinealectomy and after correction with melatonin - S. V. Michurina; I. Yu. Ishchenko; S. A. Arkhipov; A. Yu. Letyagin; M. A. Korolev; E. L. Zavjalov (Вавиловский журнал генетики и селекции)
The presence of humans and animals under long-term continuous lighting leads to a suppression of melatonin synthesis, that is, to light-induced functional pinealectomy (LIFP), and the development of desynchronosis. To create LIFP, C57Bl/6 mice were kept under 24-hour lighting (24hL) for 14 days. The animals in the control group were kept under standard lighting conditions. In the next series of experiments, mice with LIFP received daily intragastrically either melatonin (1 mg/kg body weight in 200 μl of distilled water) or 200 μl of water as a placebo. The comparison group consisted of intact animals that received placebo under standard lighting conditions. Immunohistochemical analysis (using an indirect avidin-biotin peroxidase method) revealed the expression of the antiapoptotic protein Bcl-2 and the proapoptotic protein Bad in sinusoid liver cells (a heterogeneous population consisting of the endotheliocytes, Kupffer cells, Ito cells, and Pit cells) and in individual hepatocytes. The Bad expression area in the liver of LIFP mice increased 4 times against a background of the unchanged Bcl-2 expression area. Changes in the brightness (a parameter inversely proportional to the marker concentration) of Bad and Bcl-2 areas did not reach significance. Our results indicate a weakening of the antiapoptotic protection of liver cells of LIFP animals, which creates conditions for activation of the “mitochondrial branch” of apoptosis. Melatonin treatment of LIFP mice resulted in a 3.3-fold increase in Bcl-2 expression area and a 2.7 % decrease in Bcl-2 region brightness compared with the experimental untreated group. Bad protein parameters were unreliable. Thus, melatonin treatment of animals cancels the effect of LIFP, restoring the Bcl-2 expression area and increasing this protein concentration, which indicates an increase in antiapoptotic protection and creates conditions for blocking the development of the “mitochondrial branch” of apoptosis in liver cells.